2023
DOI: 10.3324/haematol.2023.284133
|View full text |Cite
|
Sign up to set email alerts
|

Home time among older adults with acute myeloid leukemia by therapy intensity

Christopher E. Jensen,
Allison M. Deal,
Alexis C. Wardell
et al.

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…12 Prior work found that patients with AML at our institution receiving HMA-based therapy spent a mean 58% of days not engaged in oncologic care. 13,14 To date, however, no study has sufficiently compared home time of adults with AML receiving anthracycline-based regimens with HMA-based regimens. Recently, methods have been refined to capitalize on administrative data to describe home time.…”
mentioning
confidence: 99%
“…12 Prior work found that patients with AML at our institution receiving HMA-based therapy spent a mean 58% of days not engaged in oncologic care. 13,14 To date, however, no study has sufficiently compared home time of adults with AML receiving anthracycline-based regimens with HMA-based regimens. Recently, methods have been refined to capitalize on administrative data to describe home time.…”
mentioning
confidence: 99%